SENGKETA KEBERATAN DIBANDINGKAN DENGAN SENGKETA PENGADILAN PAJAK BERDASARKAN PERATURAN YANG BERLAKU - Asmorowati, Meiti (Sekolah Tinggi Hukum Bandung, 2011)
Tax Dispute is caused by dissimilarity opinion between tax payers and tax officials based on tax assessment. Therefore, it needs a protection to tax payers by giving justice through a formal and official legal channel. This legal channel is through an objection procedure proposed to pratama tax office where the tax payer is registered. Whwn there is no satisfaction, it can be brought and appealed to Court of tax which is a court outside of four kinds of judicial environments regulated in article 25, paragraph (1), Act No. 48 year 2009 on judicial authorities. The verdict of Court of tax is a final decision, but it can still be struggled by extraordinary legal efforts to the Supreme Court by reconsideration. The dispute settlement performed by Pratama Tax Office and Court of Tax is Different. The difference can be seen from authorities, the officials in charge, the place of disput settlement, procedures, and contents of decision.Keywords: Tax Dispute, objection, Court of Tax